(untitled) - DeGarmo, E. Paul (Upper Saddle River, NJ, 1997)
Often emulated but never matched, DeGarmo's Materials and Processes in Manufacturing has been the standard introduction to manufacturing fundamentals since 1957. The book has long been noted for its comprehensive coverage of the basic workings of various materials and processes. Study new processes. While this book still focuses on casting, forming, machining, and joining, new material on rapid prototyping, electronics, and metal-cutting has been added.
Keywords: Manufacturing processes.,Materials.,Qúa trình sản xuất